Isolation and characterization of a highly efficient chlorpyrifos degrading strain of Cupriavidus taiwanensis from sludge. (3rd December 2014) - Wang, Daosheng; Xue, Quan; Zhou, Xiaolei; Tang, Xinyun; Hua, Roma
Abstract In this study, a highly effective chlorpyrifos (CP)‐degrading bacterium (termed strain X1) was isolated from the sludge of drain outlet of a chlorpyrifos manufacturer. Strain X1 was identified as Cupriavidus taiwanensis based upon the analysis of the 16S rDNA gene and biochemical characteristics, which is capable of transforming CP into 3, 5, 6‐trichloro‐2‐pyridinol (TCP), and the resulting TCP was further metabolized when performed in an aqueous medium. Degradation experiments were carried out under different conditions at the range of pH (5.0∼9.0) and temperature (22∼42 °C), and the optimized pH and temperature were 7.0 and 32 °C respectively. Biotransformation of high concentration of CP was also determined; 400 mg l−1 of CP was completely transformed within 36 h; approximately 95% of CP was removed within 48 h when concentration of CP was up to 500 mg l−1. A genomic library was successfully constructed to clone the gene encoding the CP hydrolase, and a positive transformant with clear hydrolytic zones was obtained and analyzed. The insert gene sequence exhibited close relationship with 99% similar to opdB gene encoding parathion hydrolase, whereas, transformant failed in degrading the accumulated TCP. These results highlight the potential of this bacterium to be used in the cleanup of CP.